Strengthening Socio-Ecological Resilience through an Adaptive Governance Approach in Regional Environmental Management - Fatima Noor Qureshi (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study examines the strengthening of socio-ecological resilience through an adaptive governance approach in regional environmental management in Pakistan. The research investigates how institutional capacity, stakeholder collaboration, and community adaptation contribute to resilience under increasing environmental pressures associated with climate change, flooding, drought, and land degradation. Subjects and Methods: A qualitative case study design was employed in environmentally vulnerable regions of Pakistan during 2025. Data were collected through semi-structured interviews with government officials, community leaders, academics, representatives of non-governmental organizations, and local residents, complemented by field observations and document analysis. The data were analyzed using an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing. Credibility was enhanced through source and method triangulation, member checking, and peer debriefing. Results: The findings indicate that socio-ecological resilience remains at a developmental stage, characterized by relatively strong community adaptive capacity but limited institutional support. Adaptive governance strengthens resilience through policy flexibility, collaborative governance, social learning, and integration of local ecological knowledge. Nevertheless, fragmented institutions, weak policy coordination, limited cross-sector collaboration, and insufficient community participation continue to constrain governance effectiveness and long-term environmental adaptation. Conclusions: Strengthening socio-ecological resilience requires integrated adaptive governance that combines institutional reform, collaborative decision-making, continuous learning, and meaningful public participation. Such an approach provides a strategic framework for achieving sustainable regional environmental management and enhancing resilience to increasingly complex socio-ecological challenges in developing countries.